Literature Review: Practice Research - Crockett Thomas, Phil (2018)
In this paper I discuss some of the literature on arts-based practice research that seems pertinent to our project, and suggest some resources for further enquiry. I also briefly consider the parallel turn towards participation in the arts, using the work of Jeanne Van Heeswijk as an example